Extraction and evaluation of antibacterial activity from selected flowering plants - Abdullah, Erlina; Ahmad Raus, Raha; Jamal, Parveen (Science Publications, 2012)
The huge diversity of Malaysian flora has various chemical constituents that make them as outstanding natural product candidates for the treatment of infectious diseases. The screening practice for phytochemical compound in them is essential to explore more natural sources to replace synthetic antibiotics, which generally have side effects such as hypersensitivity, immune-suppression and allergic reactions. Antibacterial activities have been detected in some of the Malaysian plants and most of the Malaysian medicinal plants have been screened for this property. However, so far no study has focus on Malaysian flowering plants yet. In this study, the extraction and determination of antibacterial property from 19 Malaysian flowering plants were conducted. The plants were extracted with methanol, ethyl acetate, hexane and distilled water, individually at concentration of 0.1g mL-1. The extraction process condition was set to 300 rpm agitation for 10 h at room temperature. The crude extracts of each plant (5 mg/disc) were tested against Bacillus subtilis and Escherichia coli using agar disc diffusion assay method. The screening results showed that ethyl acetate extract of Spathiphyllum cannifolium (‘peace lily’) leaves possesses the highest antibacterial activity against B. subtilis with zone of inhibition of 25 mm. Most of the plant samples extracted with methanol and ethyl acetate have indicated positive activity toward B. subtilis growth. However, the hexane and distilled water extracts was ineffective to combat the B. subtilis growth. Unfortunately, all of the extracts were not active against E. coli. This study suggested that S. cannifolium is highly potential in antibacterial activity which can be further analyzed for the development of new antibiotic exclusively for gram positive bacteria.